2021
DOI: 10.2147/ppa.s298725
|View full text |Cite
|
Sign up to set email alerts
|

User-Centric Approach to Specifying Technical Attributes of Drug Delivery Devices: Empirical Study of Autoinjector-Cap Removal Forces

Abstract: Purpose The subcutaneous delivery of biologics using pre-filled autoinjector devices continues to attract broad scholarly interests. However, research still lacks a detailed understanding of user perceptions as the basis for specifying the clinically relevant technical attributes of a device, such as the cap-removal force. Therefore, this article studies the ability of users to remove the autoinjector cap, as well as the effects of the cap-removal force and user characteristics on the perceived ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…One exception is a study by Schneider et al (2021) that evaluated an autoinjector platform, with magnet-instrumented mockups to simulate cap removal forces of 25N, 35N, 45N, and 55N (Schneider et al, 2021). The study was tested across a wide range of populations and found that all participants were able to de-cap the devices up to 55N (Schneider et al, 2021). However, authors of the paper did note that despite the successful task completion, some participants struggled with the task.…”
Section: Cap Removal Forcementioning
confidence: 99%
“…One exception is a study by Schneider et al (2021) that evaluated an autoinjector platform, with magnet-instrumented mockups to simulate cap removal forces of 25N, 35N, 45N, and 55N (Schneider et al, 2021). The study was tested across a wide range of populations and found that all participants were able to de-cap the devices up to 55N (Schneider et al, 2021). However, authors of the paper did note that despite the successful task completion, some participants struggled with the task.…”
Section: Cap Removal Forcementioning
confidence: 99%
“… 24–26 Secondly, appropriate handling forces improve the accessibility of emerging self-care treatment options to a diverse user population. 27 This aspect is essential in the current era of self-injection device platforms. 2 , 11 , 12 The industry is adopting pre-engineered technologies to serve multiple target patient populations, including those with varying levels of strength and dexterity.…”
Section: Introductionmentioning
confidence: 99%
“… 28 Inappropriate handling forces can lead to use-related errors and jeopardize patient safety. 17 , 27 Thirdly, meeting the stringent regulatory standards for self-injection devices is critical to obtain regulatory approval and a prerequisite for successful market adoption. 29 , 30…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations